Cause Analysis of Fracture of Flange Bolts of Natural Gas Pipelines in Pressure Regulating Station - ZHOU Gong-wen (Cailiao Baohu, 2021)
The flange bolts of natural gas pipelines of a company’s public system pressure regulating station were broken. In order to find out the reason, fractured flange bolts were analyzed by macro inspection. The fracture morphology, chemical composition, metallographic structure and hardness were analyzed by field emission scanning electron microscope, X-ray fluorescence spectrometer, metallographic microscope and Brinell hardness tester. Results showed that main reasons for the fracture of the flange connection bolts were that the material was misused, and the supply state was non-quenched treatment, which was inconsistent with the design, and the bolts itself had serious opening defects, the opening defects penetrated the screw to the thread, and the deepest radial to the bolts center. During operation, the middle part of the screw bore a large pre-tensioning force and torsional shear force. In the middle of the screw, the crack tips propagated rapidly along the grain boundary defects until brittle fracture. Finally, the corresponding suggestions were proposed.